Evolutionary Game Analysis of Construction Risk Management of Subcontracting Project under EPC Mode - Gong, Tingxin; Jin Chen; Wenrui Feng; Zaohong Zhou; Yunbin Sun; Hongyan Chen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper develops a two-party evolutionary game model between the general contractor and the construction subcontractor under the Engineering-Procurement-Construction (EPC) mode to determine the positivity of strict management by the general contractor as well as high standards of production by the subcontractor under different social and production conditions. The results show that whether the game system converges to the ideal Evolutionary Stable Strategy (ESS) depends on both parties’ benefits in the project, reputation value in the industry, additional losses incurred by defaults, and supervision costs. In the process of EPC project construction risk management, each game party should clarify contractual responsibilities, set specific penalties, build an information disclosure platform, evaluate performance regularly, and establish a reward system based on quality to promote the sustainable and healthy development of the EPC project mode.